An Analysis of Illocutionary Acts Used in Joe Biden’s Speech Before the 77th Un General Assembly - Dyah Ayu Caesar Qutsy; Dias Andris Susanto; Dyah Nugrahani (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The study analyzes illocutionary acts in Joe Biden's speech at the 77th UN General Assembly using Yule's (1996) and Leech's (1983) theories. The data from the UN YouTube channel and the White House website, underwent descriptive qualitative analysis. A total of 72 illocutionary acts were Identified. The data set comprised 39 representatives (54.17%), 17 directives (23.61%), 11 commissive (15.28%), 3 expressive (4.16%), and 2 Declarative (2.78%). The functions were 78.38% collaborative, 10.81% conflictive, 8.11% convivial and 2.70% competitive. The findings indicate the predominant use of representative acts to convey information and collaborative functions to express concerns and report challenges.